Efficacy of pre-emergent herbicides on weed dynamics, productivity and profitability of wheat (Triticum aestivum L.) in North Western Himalayan region - Rakesh , Kumar; Faraaz , Farooq; Shubham , Jamwal; Banti; Vivek , Bhagat; Neetu , Sharma; Meenakshi , Gupta; Ramphool , Puniya; Dwivedi, M C (Plant Science Today, 2025)
Weed infestation is one of the major threats to crop productivity and ineffective management can exacerbate the issue. Under these circumstances, using highly effective broad-spectrum herbicides is the only viable way to supress weeds. With this aim, a field experiments were conducted at Research Farm of Sher-e-Kashmir University of Agricultural Sciences and Technology, Jammu during rabi season 2021-22 and 2022-23 with twelve treatments on sandy clay loam soil in randomized block design (RBD), replicated thrice. The results revealed that weed free plot gave higher growth and yield attributes viz., plant height (100.05 cm), dry matter accumulation (1309.22 g m-2), effective tillers (459.64 m-2), grain spike-1 (47.26), test weight (42.76 g), grain yield (5377.67 kg ha-1) and straw yield (7842.68 kg ha-1) fb pendimethalin + metribuzin @ 1250 + 280 g a.i. ha-1 (PE tank mix). The pendimethalin + metribuzin @ 1250 + 280 g a.i. ha-1 (PE tank mix) recorded significantly higher weed control efficiency (90.75 and 90.82 %), lower weed density (4.12 and 4.21 m-2), weed biomass (2.59 and 4.97 g m-2) at 30 and 60 DAS, respectively and lower weed index (10.35 %) as compared to weedy check plot. Maximum gross returns (147573.36 ? ha-1) and net returns (107206.86 ? ha-1) were recorded under weed free plot but highest B: C ratio (3.37) was achieved in pendimethalin + metribuzin @ 1250 + 280 g a.i. ha-1 (PE tank mix). Moreover, no phytotoxicity symptoms were seen in any of the treatment in the succeeding crop.